(3eNJUQ WHbGJ GdMfajIs - (3Ydj Hf CeQ Gddg GdLfGFis; (3YHO GdbGOQ GdbQTj,J (B775 (3g` s
(3ChdgG (B:s
(3HOG HJQLeI GdEeGe CHhMfjaI s
(3BNQgG (B:s
(3JQLeI Gdehdi CMeO Hf SdjeGf s
(3PcQ UGMH WHbGJ GdYHGO Cfg JCdja QajY GdOjf GdTjQGRis
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B42s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B266 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1099s
Keywords: (3GdJGQjNs